2011
DOI: 10.1159/000321201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opium Dependency on Burn Healing in a Rat Model: An Experimental Study

Abstract: Objective: This study aimed to investigate the effect of opium dependency on the healing of third-degree burns in rats. Material and Methods: Twenty-four rats were randomly divided to experimental and control groups. In the experimental group, opium was added to the drinking water for 21 days at increasing concentrations. The control group did not receive opium. To prove dependency on opium in the rats, naloxone was injected intraperitoneally. Full-thickness burn wounds were inflicted by applying an iron cuboi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In our case, the burned areas were more extensive than those reported by Sedighi; and they were younger. There is an incorrect assumption that opium not only reduces the burns pain but also prolongs the time required for the rehabilitation [20]. The parents in both our and Sedighi's cases denied having any knowledge about the potentially fatal adverse effects of using opium in children and the possibility of its absorption from the injured skin.…”
Section: Discussionmentioning
confidence: 84%
“…In our case, the burned areas were more extensive than those reported by Sedighi; and they were younger. There is an incorrect assumption that opium not only reduces the burns pain but also prolongs the time required for the rehabilitation [20]. The parents in both our and Sedighi's cases denied having any knowledge about the potentially fatal adverse effects of using opium in children and the possibility of its absorption from the injured skin.…”
Section: Discussionmentioning
confidence: 84%
“…There are few studies on possible impact of opium on wound healing (5). In addition, based on our clinical experience we noticed that wound healing process can also be impacted by chronic opium usage; and in depended patients we noticed a better tolerance of postoperation course and wound healing.…”
Section: Introductionmentioning
confidence: 71%
“…In vitro study, it was concluded that nalbuphine, a semisynthetic opioid, damages stromal fibroblasts and corneal epithelium, thereby adversely affecting wound healing 14 . In another study, it was observed that the number of myofibroblasts and macrophages decreased in the tissue samples taken in the proliferative phase in burned morphine-addicted rats 6 . In the present study, unlike other studies, fibroplasia increased statistically significantly in the proliferative phase, especially in the 2nd week.…”
Section: Discussionmentioning
confidence: 92%
“…Many more studies such as these have examined the effects of different opioids on wound healing, depending on duration and dose. There are data with positive and negative findings, but most wound healing studies are skin-focused [2][3][4][5][6][7][8] . However, for an optimal wound healing, especially in the abdominal wall, the fascial layer, which is the main load bearing part, must be complete.…”
Section: Introductionmentioning
confidence: 99%